2015
DOI: 10.1002/anie.201508180
|View full text |Cite
|
Sign up to set email alerts
|

Cyclization of Pyrene Oligomers: Cyclohexa‐1,3‐pyrenylene

Abstract: First synthesis of the macrocycle cyclohexa(1,3-pyrenylene) is achieved in six steps starting with pyrene, leading to a non-aggregating highly twisted blue-light-emitting material. The cyclodehydrogenation of the macrocycle offers a promising synthesis route to holey-nanographene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Introduction p-Conjugated macrocycles with well-dened diameters have received signicant attention in the last few decades, mainly because of their unique optical and electronic properties, their host-guest capabilities, and their potential as building blocks for supramolecular materials. [1][2][3][4][5][6] Many p-conjugated macrocyclic systems aggregate into columnar structures, 4,7-11 producing molecular channels that, with the appropriate inner-core functionalization, may give rise to ion channels, rod-like micellar aggregates, and even reaction chambers. [12][13][14][15] A particularly intriguing class of p-conjugated macrocycles is macrocyclic oligothiophenes (C-nT, Chart 1), introduced by Bäuerle's group in sizes ranging from C-8T to C-35T.…”
mentioning
confidence: 99%
“…Introduction p-Conjugated macrocycles with well-dened diameters have received signicant attention in the last few decades, mainly because of their unique optical and electronic properties, their host-guest capabilities, and their potential as building blocks for supramolecular materials. [1][2][3][4][5][6] Many p-conjugated macrocyclic systems aggregate into columnar structures, 4,7-11 producing molecular channels that, with the appropriate inner-core functionalization, may give rise to ion channels, rod-like micellar aggregates, and even reaction chambers. [12][13][14][15] A particularly intriguing class of p-conjugated macrocycles is macrocyclic oligothiophenes (C-nT, Chart 1), introduced by Bäuerle's group in sizes ranging from C-8T to C-35T.…”
mentioning
confidence: 99%
“…[9] The next large acene unit suitable for hexagonal design is 2,7-anthrylene, and such frameworks as [6]cyclo-2,7-anthrylene ( [6]CANT, r = 1.97 nm) have been unknown to the best of our knowledge. [10][11][12] The studies of [6]CNAPi ndicated that in order to synthesize such al arge macrocycle, its structure should be modified so that reasonable solubility is maintained. In the courseo fo ur studies of anthracene-acetylene oligomers, [13] we found that bulky mesityl (Mes) groups on an anthracene unit reasonably improved the solubility and stability because those groups protected the aromatic cores from intermolecular stacking and undesired reactions.…”
mentioning
confidence: 99%
“…Most of the described in literature pyrenes are 1,3,6,8-tetrasubstituted followed by 4,5,9,10-tetrasubstituted, 2,7-, and 1,6-, and 1,8-disubstituted pyrene derivatives [2][3][4][5]. In the case of 1,3-di(hetero)aryl-7-substituted ( Figure 1), there are only a few examples of derivatives containing at position 7-tert-butyl group [6][7][8][9]. These compounds exhibit interesting optical properties what caused that they were studied for use in the area of organic electronics.…”
Section: Introductionmentioning
confidence: 93%